TRANSFORMASI KEBIJAKAN PENGELOLAAN PENDIDIKAN DASAR, PERKEMBANGAN, HAMBATAN, DAN IMPLEMENTASI DI ERA MODERN - Hafiz Hidayat; Mulya Syafrina; Wendri Gusdi; Febrio Rozalmi Putra; Yusparni Yetti; Putri Yulia Mandasari; Seri Sufani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Primary education policy in Indonesia continues to shift in response to modernization, decentralization, and the need to improve learning quality. This literature review examines the development of basic education management policies, their implementation in schools, and the major obstacles encountered, including disparities in resources, weak governance, and limited teacher competencies. Findings show that although policy transformations have expanded school autonomy and improved curriculum standards, unequal implementation remains a critical challenge. This article concludes by offering recommendations to strengthen governance, increase teacher capacity, and improve policy alignment across government levels.